Pembentukan Medical Team melalui Person Centered Therapy dalam Pencegahan COVID-19 Fase Era New Normal di Pondok Pesantren Miftahul Mubtadiin Ar-Ridlo Krempyang Tanjunganom Nganjuk - M. Burhanuddin Ubaidillah; Yaziidul Khooiri (Janaka, Jurnal Pengabdian Masyarakat, 2020)
The phenomenon of Tha'un, Coronavirus Disease (COVID-19), which is caused by the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) virus and spreads throughout the world, especially in Indonesia, was first announced by President Jokowi on April 10, 2020. The higher the percentage of infected patients, the community becomes solitary and even paranoid. The absence of a vaccine that effectively treats COVID-19, gave birth to laws, government regulations, manuals and technical guidelines for official state ministries as preventive steps to increase fear in the community. This article aims to describe preventive steps in preventing COVID-19 by forming a Medical Team through Person Centered Therapy in the New Normal Era at the Ar-Ridlo Krempyang Tanjunganom Nganjuk Miftahul Islamic Boarding School. The results show that this program can help address problems of prevention, personal development and alleviation of problems; the practice arena changes behavior to be more satisfying; where Medical Team members learn social skills, and increase individual motivation to work through intensive and dynamic interactions in groups in the prevention of COVID-19.